Crimes Related to Violation of Regulation Relations among the Members of the National Guard of the Ministry of Internal Affairs of the Republic of Kazakhstan - TELEUZHANOV, Sanat Kerimovich (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505//jarle.v9 3(33).41, 2018)
The presented article deals with criminal offences related to non-statutory relations, which take place among the members of the National Guard of the Ministry of Internal Affairs of the Republic of Kazakhstan. Despite the statistics data showing a steady reduction in this category of crimes, there are reasons to believe that their negative impact on the state of armed forces in general, and the National Guard units of the Republic of Kazakhstan, in particular, still remains significant. Therefore, studies of the characteristics of criminal acts of this type are necessary to find the ways to combat unauthorized crime until it is completely eliminated. The author's goal is to develop the most effective criminal and legal measures to combat criminal offences related to non-statutory relations. The author draws attention to numerous reports on occurrence of non-statutory relations in the mass media, quotes data of legal statistics on criminal prosecution for the commission of relevant criminal offences, considers legislative decisions in the sphere of responsibility for committing the mentioned criminal acts, investigates reasons, ways and motives of their commission. Numerous studies of the phenomenon of non-statutory relations in the troops as well as foreign experience in combating this phenomenon are analyzed. The research allowed the author to allocate a separate group of criminal offences related to non-statutory relations from the number of military criminal offenses formed on the basis of violence as a way of committing them. Concrete proposals on improvement of criminal legislation regulating responsibility for criminal offences connected with non-statutory relations are formulated and presented.